Extracorporeal ShockWave Treatment vs. mesotherapy in the treatment of myofascial syndromes: a clinical trial - Scaturro, Dalila; Migliorino, Domenico; Lauricella, Lorenza; Quartararo, Francesco; Calabrese, Noemi; Tomasello, Sofia; Vecchio, Michele; Letizia Mauro, Giulia (Frontiers in Medicine, 2024)
Numerous scientific papers have compared different treatment options in the management of myofascial pain syndrome. This study evaluated the efficacy of Extracorporeal ShockWave Treatment (ESWT) and mesotherapy in patients with Myofascial Pain Syndrome (MPS) in terms of improvement in pain, functional capacity, and quality of life. A case–control study was conducted on 54 patients, who were randomized into 2 groups: group A, consisting of 27 patients, who were treated with 5 sessions of focal ESWT on a weekly basis; and group B, consisting of 27 patients, who underwent 5 sessions of mesotherapy with Thiocolchicoside fl 4 mg/2 mL and Mepivacaine fl 10 mg/1 mL on a weekly basis. Patients were evaluated at enrollment (T0), after 5 weeks, at the end of rehabilitation treatment (T1), and at a follow- up 30 days after the end of treatment (T2), by administering rating scales (Numeric Rating Scale (NRS) - Pressure Pain Threshold (PPT) – Short Form-36 (SF-36)). The results showed that focal ESWT and Mesoterapy are two valid and effective treatment options in reducing algic symptoms and improving short- and long-term quality of life. However, the use of ESWTs, despite being mildly painful but tolerated, has been shown to be superior to mesotherapy in terms of pain reduction and increased functional capacity.